Defrosting Performance Improvement of Air-Source Heat Pump Combined Refrigerant Direct-Condensation Radiant Floor Heating System with Phase Change Material - Chenxiao Zheng; Shijun You; Huan Zhang; Zeqin Liu; Wandong Zheng; Zhenjing Wu; Man Fan (Energies, 2020)
Traditional defrosting methods applied to solve frosting problems of air-source heat pumps operating in cold periods may reduce heat capacity of the system and decrease indoor thermal comfort. In order to improve the performance of air-source heat pump (ASHP) and maintain indoor temperature in defrosting conditions, an air-source heat pump combined with a refrigerant direct-condensation radiant floor heating system with phase change material is proposed and evaluated in this study. Two radiant floor heating terminals with and without composite phase change material modules were compared through experiments. A composite phase change material based on dodecanoic acid-tetradecanol-hexadecanol mixture and expanded graphite was investigated for this application. Experimental results indicate that both heat fluxes of two comparing terminals are higher than 70 W/m2 in heating condition. At the same time, the floor surface temperature, indoor air temperature, and heating capacity of the terminal with composite phase change material modules are higher than those without composite phase change material modules in defrosting condition. This suggests that the proposed system with composite phase change material modules can improve indoor thermal comfort in defrosting condition as well as satisfy the heating requirement in heating condition.